PEMANFAATAN LIMBAH PLASTIK UNTUK STEAM ANAK-ANAK SEKOLAH DASAR - Ariyanto, Lilik; Wulandari, Dewi; Ma'mun, Hisyam; Torisafiar, Fifi; Rosario, Marcel Adventino Rendra (LPPI UMN AL WASHLIYAH, 2024)
Plastic waste is increasingly difficult to control, particularly plastic beverage bottles and food packaging. This undoubtedly necessitates prompt action to mitigate the detrimental effects of plastic on the environment. The objective of this activity is to enhance the skills and abilities of utilising plastic waste for games and learning, thereby reducing environmental pollution caused by plastic waste in the living environment. The implementation of this plastic STEAM PKM activity employs a training methodology for children to create manual props for games and learning using plastic waste. Children are encouraged to analyse their own needs by watching STEAM media creation reference videos (Analysis), design the tools they wish to create, including preparing the necessary plastic materials (Design), realise the Design (Development), utilise the tool (Implementation), and provide feedback on their own work and that of their peers (Evaluation). The outcomes of the activity included the enthusiasm and eagerness of the 23 elementary school children who participated in the training, as evidenced by their keenness to create and learn to utilise plastic waste